Transarterial Embolization in Neonatal Kasabach–Merritt Syndrome - Yinghao Wang (Frontiers Media S.A., 2021)
Background: Kasabach–Merritt syndrome (KMS) is characterized by large hemangiomas and persistent thrombocytopenia, which may result in visceral hemorrhage and disseminated intravascular coagulation. This study aimed to evaluate the value of transarterial embolization (TAE) in neonatal KMS patients.Patients and Methods: The clinical course of 11 neonates with KMS who underwent TAE in the Department of Neonatology, Anhui Provincal Children's Hospital, Anhui Medical University, China, were reviewed retrospectively.Results: Eleven neonates with KMS (nine male and two female) were admitted to our hospital between the age of 1 h and 6 days. All were born with progressively enlarged hemangiomas and persistent thrombocytopenia. The largest lesion had its maximum size reached at 15 × 8 × 8 cm. Eight patients had cutaneous hemangiomas (1 right face, one oropharynx, one left upper arm, two back, one left lumbar, one right lower leg, and one right thigh), and three patients had liver hemangiomas. All 11 patients underwent TAE. Nine patients underwent two TAEs, and two patients underwent only one embolization procedure. They all obtained >80% devascularization of their lesions without a major complication. The platelet count increased at 2–5 days after treatment and reached normal count and coagulation profile at 18–28 days after the TAE.Conclusions: TAE is a safe and effective alternative therapy for neonatal KMS patients.